101k views
0 votes
Find the distance between the points (-2,6) and (-1,-3)

2 Answers

5 votes

Answer:

9.06

Explanation:

(-2,6) and (-1,-3)

Distance =√(x2−x1)^2+(y2−y1)^2

√(−1−(−2))^2+(−3−6)^2

√(1)^2+(−3−6)^2

√(1)^2+(−9)^2

√1+81=

√82 ≈9.055385138137417

User SiN
by
5.7k points
3 votes

Answer:


√(82)

Explanation:

Calculate the distance d using the distance formula

d =
\sqrt{(x_(2)-x_(1))^2+(y_(2)-y_(1))^2 }

with (x₁, y₁ ) = (- 2, 6) and (x₂, y₂ ) = (- 1, - 3)

d =
√((-1+2)^2+(-3-6)^2)

=
√(1^2+(-9)^2)

=
√(1+81)

=
√(82) ≈ 9.06 ( to 2 dec. places )

User Ajrwhite
by
5.7k points